A phytochemical investigation of Stemona parviflora roots reveals several compounds with nematocidal activity. (March 2019) - Huang, Sheng-Zhuo; Kong, Fan-Dong; Chen, Gao; Cai, Xiang-Hai; Zhou, Li-Man; Ma, Qing-Yun; Wang, Qi; Mei, Wen-Li; Dai, Hao-Fu; Zhao, You-Xing
ABSRACT: Twelve undescribed compounds including six phenanthrene derivatives (parviphenanthrines A-F), two stilbene derivatives (parvistilbines A-B), three esters (parviesters A-C), and one sesquiterpenoid (parvidiol A) were isolated from the roots of Stemona parviflora, together with twenty-two known ones. The structures of the undescribed compounds were elucidated based on the analyses of their spectroscopic data. The absolute configuration of parviphenanthrine A was determined by the quantum ECD calculations. Parviphenanthrines A and E, stemanthrene A, stilbostenin E, 4-hydroxy-benzenepropanol- α -benzoate, and ( E )-4-hydroxycinnamic acid methyl ester showed nematocidal activity against Meloidogyne incognita with IC50 values of 14.02 ± 0.32, 2.51 ± 0.13, 17.10 ± 0.65, 2.05 ± 0.07, 4.22 ± 0.31, and 1.07 ± 0.05 μ M, respectively. Graphical abstract: Highlights: 34 non-alkaloids, including twelve undescribed ones, isolated from Stemona parviflora. The phytochemicals from Stemona genus were categorized into 11 structural classes. The phenols were also the main bioactive constituents with nematicidal bioactivity. The phenols showed better safety profiles than alkaloids.